DAMPAK NEGATIF DUNIA MAYA DALAM BAGI PERKEMBANGAN TEKNOLOGI INFORMASI DI INDONESIA - Eni Irfiani (Paradigma, 2008)
The need of using computers that are connected one with another in 1969 opens a path to global interaction between users through internet technology. Internet development also influences the development of information technology in Indonesia. Up to 4.2 million people of Indonesia have made use of the internet. On one hand, it is useful for users. On the other hand, it opens possibilities for cyber crimes. Yet Indonesia has not had any force of law governing cyber crimes.